Enhancement and evaluation in path accuracy of industrial robot for complex surface grinding. (June 2023) - Li, Jiangyang; Zou, Lai; Luo, Guoyue; Wang, Wenxi; Lv, Chong
Highlights: A novel path accuracy enhancement strategy and different evaluation methods of an industrial robot FANUC M710ic/50 are proposed for complex surface grinding of aero-engine blade. A revised Levenberg-Marquardt and Differential Evolution hybrid algorithm is proposed by considering several parameters of path planning to improve robotic absolute positioning accuracy. The evaluation methods MP-TLD, BP-TPD and the MP-TID with different calculation principles are proposed to conclude that this typical industrial robot with an average path accuracy value of approximately 0.035 mm. Abstract: Lower path accuracy is an obstacle to the application of industrial robots in intelligent and precision grinding complex surfaces. This paper proposes a novel path accuracy enhancement strategy and different evaluation methods for a six-degree-of-freedom industrial robot FANUC M710ic/50 used for grinding an aero-engine blade. Six groups of theoretical tool paths individually planned on this complex surface were obtained using the iso-parametric method and the constant chord height method. Then the actual paths of the robot were dynamically recorded by a laser tracker with a high frequency. A revised Levenberg-Marquardt and Differential Evolution hybrid algorithm was proposed to improve the absolute robotic positioning accuracy by considering the average curvature variation rate, the arc length and the number of cutter contact points on planning paths. The results showed that the maximum positioning error had been drastically reduced from 0.792 mm to 0.027 mm. Based on the redefinition of robotic path accuracy, including position accuracy and shape accuracy in this work, the methods MP-TLD, BP-TPD and MP-TID were proposed to evaluate the enhanced path accuracy. The evaluation results showed that the different path planning methods have almost little effect on path accuracy. Furthermore, the maximum path deviation evaluated by the MP-TLD method was reduced from 0.378 mm to 0.044 mm, evaluated by the BP-TPD method was reduced from 0.374 mm to 0.029 mm, and evaluated by the MP-TID method was reduced from 0.205 mm to 0.026 mm. It is concluded that these evaluation methods are basically valid and the average path accuracy value is about 0.035 mm, for present complex surface grinding with this typical industrial robot. Finally, the robotic grinding experiments of titanium alloy blades are conducted to further validate the effectiveness of the proposed method.